Can anti-illegal, unreported, and unregulated (IUU) fishing trade measures spread internationally? Case study of Australia. (1st March 2021) - Garcia Garcia, Sonia; Barclay, Kate; Nicholls, Rob
Abstract: The emergence of illegal, unreported and unregulated (IUU) fishing as a policy issue over the past two decades has galvanised efforts to advance the regulation of high seas fishing to ensure the conservation and sustainable use of fishery resources. This process enabled the introduction of environmental provisions into international trade under the guise of ensuring the lawful sourcing of seafood. This has proven more acceptable to the trade regime than bans on unsustainably harvested seafood. The European Union and the United States have led the establishment of legality as a proxy for different environmental and social accountability concerns and have implemented unilateral trade measures to prevent seafood sourced from IUU fishing from entering their markets through traceability schemes. Although the EU and US are huge markets, the ultimate success of such measures in reducing IUU fishing lies in their take up in other countries and the potential for harmonisation at the supra-state level. This research has explored the potential for implementation of anti-IUU trade measures in Australia through discourse analysis of semi-structured interviews and public policy documents. Our findings show that there is very limited potential for anti-IUU fishing trade measures in Australia due to socio-specific constructions of IUU and of fisheries management. These findings are relevant for the potential policy diffusion of anti-IUU trade measures in market states. Highlights: Illegal, unreported and unregulated (IUU) fishing is a policy and trade issue. Unilateral measures on IUU fishing are compatible with international trade regimes. Discursive analyses reveal socio-specific constructions of IUU fishing as a problem. IUU fishing policy is bounded by problem characterisation. Australia shows limited potential to adopt anti-IUU unilateral trade measures.